Spectral Radiometric Measurements of Sub-Arctic Stratospheric Constituents - Murcray, David G; Goldman, Aaron; Kosters, John J; Murcray, Frank H; Williams, Walter J (1978)
Constituent height profiles are derived for HNO3, O3, H2O, CF2Cl2, CFCl3 and two unidentified constituents from spectral radiance data observed on a balloon flight to 37.56 km on 29 April 1976 from Fairbanks, Alaska. Improvements in the band model techniques used are discussed and comparative results are shown. Spectral radiance data observed at selected altitudes and zenith angles are shown covering the spectral ranges of 8 to 13.6 micron and 18. 8 to 27.6 micron. Tables of spectral radiance for selected spectral regions as a function of altitude are included. See also Rept. no. BRL-CR-332 dated Feb 1977, ADA037375.